INTERNET USAGE AMONG ADOLESCENTS: A STUDY OF HIGHER SECONDARY STUDENTS IN IMPHAL WEST DISTRICT OF MANIPUR - Devi, Anoubam Victoria; Devi, Konjengbam Rashitombi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The world witnesses a massive surge of internet users in the post Covid-19 global pandemic, particularly among adolescent students for various purposes and is integral to their social and educational life. Keeping this in view, the aim of the present study was to examine the internet usage of higher secondary students in the Imphal West District of Manipur and an attempt has also been made to compare the differences in internet usage of higher secondary students based on their gender and social categories. The descriptive research method was adopted to study the internet usage of 100 (male=53, female=47) randomly selected higher secondary students from three schools in Imphal West District of Manipur. The Internet Usage Scale (IUS-SSKP, 2017) developed by Shaloo Saini and Prof. (Dr.) Parminder Kaur (2017) was used to measure the internet usage of higher secondary students. Hypotheses were tested using a t-test and ANOVA (2-tailed at 0.05 significance level). The result reveals that higher secondary students have an average level of Internet usage and confirmed a clear increasing trend of internet usage among students. The higher secondary school of Imphal West District of Manipur is not influenced by their gender and social category. The study suggested the integration of internet-based tools in the classroom, promoting digital literacy programs and addresses gaps in internet usage, and informing educators, school administrator, policy makers and parents about the patterns of internet usage and digital behaviors of adolescent students.